2019
DOI: 10.1002/anie.201909675
|View full text |Cite
|
Sign up to set email alerts
|

Palladium–Borane Cooperation: Evidence for an Anionic Pathway and Its Application to Catalytic Hydro‐/Deutero‐dechlorination

Abstract: Metal–Lewis acid cooperation provides new opportunities in catalysis. In this work, we report a new type of palladium–borane cooperation involving anionic Pd0 species. The air‐stable DPB palladium complex 1 (DPB=diphosphine‐borane) was prepared and reacted with KH to give the Pd0 borohydride 2, the first monomeric anionic Pd0 species to be structurally characterized. The boron moiety acts as an acceptor towards Pd in 1 via Pd→B interaction, but as a donor in 2 thanks to B‐H‐Pd bridging. This enables the activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 64 publications
2
27
0
Order By: Relevance
“…The 11 B NMR resonances are shifted linearly towards higher field with an increasing Pd,B distance for Pd 0 complexes, regardless of the valence electron count at the Pd center (Figure ). Complex [( Ph DPB Ph )Pd 0 (PPh 3 )] ( 2 ) reported by Kameo and Bourissou also fits perfectly into this correlation (d(Pd,B)=2.294(2) Å, δ ( 11 B) 27 ppm). In contrast, the 11 B NMR resonance shifts linearly towards lower field with an increasing Pd,B distance in case of Pd II complexes.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The 11 B NMR resonances are shifted linearly towards higher field with an increasing Pd,B distance for Pd 0 complexes, regardless of the valence electron count at the Pd center (Figure ). Complex [( Ph DPB Ph )Pd 0 (PPh 3 )] ( 2 ) reported by Kameo and Bourissou also fits perfectly into this correlation (d(Pd,B)=2.294(2) Å, δ ( 11 B) 27 ppm). In contrast, the 11 B NMR resonance shifts linearly towards lower field with an increasing Pd,B distance in case of Pd II complexes.…”
Section: Resultssupporting
confidence: 70%
“…Thus, facile access to complexes featuring transition metals with formally negative oxidations states is realized (Figure a) . This stabilization of low oxidation states appears to inhibit oxidative addition reactions . However, we demonstrated that this obstacle can be overcome for complex 1 by addition of catalytic amounts of acetate, which competes with Pd 0 for the free coordination site at the borane, thus reversibly breaking the Pd 0 →B interaction (Figure b) .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…37 Recently, Kameo and Bourissou reported another type of Pd-B cooperation involving anionic Pd species in a hydrodechlorination reaction of aryl chlorides. 38 The reaction of a Pd complex 17 having a Z-type PBP-ligand with KH and [2.2.2]cryptand afforded an anionic Pd complex 18, which possessed a bridging hydride ligand between Pd and B (Scheme 5). The anionic Pd complex 18 smoothly reacted with chlorobenzene to give benzene and the neutral Pd-B complex 17 whereas the same oxidative addition of PhCl to 17 did not proceed at all.…”
Section: Group 13 (E ¼ B Al Ga and In)mentioning
confidence: 99%
“…[ 27 ] Subsequently, Z‐type ligands based on the element boron were incorporated in pincer‐type complexes, [ 28–42 ] and used as catalysts in reactions like (de)hydrogenations. [ 34,38,43–45 ]…”
Section: Coordination Patterns With Non‐metal Ligating Atomsmentioning
confidence: 99%